Archangelolide: A sesquiterpene lactone with immunobiological potential from Laserpitium archangelica - Rimpelová, Silvie; Jurášek, Michal; Peterková, Lucie; Bejček, Jiří; Spiwok, Vojtěch; Majdl, Miloš; Jirásko, Michal; Buděšínský, Miloš; Harmatha, Juraj; Kmoníčková, Eva; Drašar, Pavel; Ruml, Tomáš (Beilstein journal of organic chemistry, 2019)
Sesquiterpene lactones are secondary plant metabolites with sundry biological effects. In plants, they are synthesized, among others, for pesticidal and antimicrobial effects. Two such compounds, archangelolide and trilobolide of the guaianolide type, are structurally similar to the well-known and clinically tested lactone thapsigargin. While trilobolide has already been studied by us and others, there are only scarce reports on the biological activity of archangelolide. Here we present the preparation of its fluorescent derivative based on a dansyl moiety using azide-alkyne Huisgen cycloaddition having obtained the two sesquiterpene lactones from the seeds of Laserpitium archangelica Wulfen using supercritical CO2 extraction. We show that dansyl-archangelolide localizes in the endoplasmic reticulum of living cells similarly to trilobolide; localization in mitochondria was also detected. This led us to a more detailed study of the anticancer potential of archangelolide. Interestingly, we found that neither archangelolide nor its dansyl conjugate did exhibit cytotoxic effects in contrast to the structurally closely related counterparts trilobolide and thapsigargin. We explain this observation by a molecular dynamics simulation, in which, in contrast to trilobolide, archangelolide did not bind into the sarco/endoplasmic reticular calcium ATPase cavity utilized by thapsigargin. Last, but not least, archangelolide exhibited anti-inflammatory activity, which makes it promising compound for medicinal purposes.
Keywords: anti-inflammatory properties; sarco/endoplasmic reticulum calcium ATPase; archangelolide; dansyl fluorescent conjugate; sesquiterpene lactone; trilobolide analogue